JONATHAN EDWARDS ON THE TRINITY - Crisp, Oliver 1972- (2014)
There was a time in the mid-nineteenth century when Jonathan Edwards was rumored to have held an Arian or even incipient Sabellian view of the doctrine of God. Now, he is lauded as a Trinitarian theologian, a divine for whom the persons of the Godhead were a touchstone for all other doctrines. Yet, although his orthodoxy is endorsed by almost all scholars at work on his corpus the form of his doctrine of the Trinity is the subject of an ongoing scholarly debate. Much of this depends on whether his views were commensurate with standard models of the Trinity, or whether he developed his own ideas in such a way as to move beyond perorations of the doctrine to which theologians have historically been held accountable.
Keywords: American Religious History; Early Modern History; Philosophy